Validation of the abbreviated Lubben Social Network Scale (LSNS‐6) and its association with self‐rated health amongst older adults in Puerto Rico. (30th August 2022) - Buckley, Thomas D.; Becker, Todd D.; Burnette, Denise
Abstract: Social isolation is a well‐established determinant of late‐life well‐being, and it may be particularly relevant for older adults in Puerto Rico following Hurricane María. The abbreviated Lubben Social Network Scale (LSNS‐6) is a widely used measure of social isolation, but it has not been validated with Spanish‐speaking older adults. The objectives of this study were to (1) assess the psychometric properties of a Spanish‐language LSNS‐6 and (2) examine its association with self‐rated health (SRH) and psychological sense of community (PSOC). Data came from face‐to‐face survey interviews with a nonprobability sample of 154 community‐dwelling older adults in Puerto Rico 2 years after Hurricane María. We assessed the LSNS‐6's internal consistency reliability and convergent validity. We then conducted structural equational modelling consisting of (1) a measurement model using confirmatory factor analysis to test the factor structure of the LSNS‐6 and (2) a structural model using path analysis to examine the direct effect of social isolation on SRH and to test the role of PSOC as a mediator in this relationship. The LSNS‐6 demonstrated acceptable internal consistency reliability ( α  = 0.74) and convergent validity, r (151) = −0.33, p  < 0.001. A correlated two‐factor model (Family and Friends) provided the best fit (comparative fit index = 0.986, Tucker–Lewis index = 0.975, root mean square error of approximation = 0.082, standardised root mean squared residual = 0.033). Path model results show the Friends factor was negatively associated with SRH ( β  = −0.31, p  = 0.045), whilst the Family factor was nonsignificant. The Friends factor had a statistically significant indirect effect on SRH through PSOC ( β  = 0.08, 95% CI [0.01, 0.29]). Our findings provide insight into the effect of social isolation on health amongst older adults in Puerto Rico and highlight the potential role of PSOC for assessment and intervention with older adults in post‐disaster settings.